The Austral-Magallanes Basin (Southern Patagonia): A synthesis of its stratigraphy and evolution. (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Austral-Magallanes is an oil-producing basin located in southern Argentina and Chile, containing a siliciclastic stratigraphic record ranging from the Late Jurassic to late Cenozoic. This short paper finalize the two special volumes of the Latin American Journal of Sedimentology and Basin Analysis dedicated to the basin, and aims to provide a comprehensive synthesis based on the current knowledge about the chronology of deposition, stratigraphy, and tectonic events that shaped this basin. During the breakup of Gondwana in the Jurassic, an extensional phase was responsible for the beginning of accumulation of volcaniclastic material within grabens, which subsequently were covered by widespread Lower Cretaceous shallow and deep marine deposits that conforms the main hydrocarbon system. From Late Cretaceous onward, the subduction-related compressive regime associated to Andean uplift and fold and thrust belt migration was responsible for the onset of the foreland stage. During the Late Cretaceous, the foredeep zone accumulated a thick pile of deep marine deposits that graded upward to shallow marine and terrestrial deposits. During the Cenozoic, the foredeep was less marked and shallow marine and terrestrial sediments accumulated in wide areas, punctuated by important unconformities associated to foreland uplift. Future developments should focus on: i) improving the age-controlled stratigraphy; ii) joining the information provided by subsurface and outcrop studies; and iii) developing source to sink models to address the Andean impact in the sedimentation of the basin.